2007
DOI: 10.1002/app.26609
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of functionalized triblock polymer: The prepared polymer is cholesteryl terminated and chain‐extended PCL

Abstract: The functionalized triblock polymer for the preparation of self-assembly biomaterials, Chol-(CL) n -Chol, was synthesized through ring-opening polymerization of ecaprolactone (e-CL) following by chain-extension reaction. The chemical structure of functionalized triblock polymer was confirmed by Fourier transform infrared and 1 H-NMR. The molecular weight of the functionalized polymer increased with decreasing feed ratio of the initiator cholesterol (Chol) to the monomer e-CL. Liquid crystalline properties and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Drug-release properties were evaluated in vitro, and the incorporation of Chol moiety in the Chol-PCL conjugate was found to improve cell proliferation. Additionally, PCL with a Chol moiety at both ends has been synthesized by coupling two monofunctional Chol-PCL conjugates to one hexamethylene diisocyanate [145]. This bifunctional conjugate has proven to be miscible with high MW PCL and thus is expected to be useful for the modification of PCL-based biomaterials.…”
Section: Cholesterol (And Other Terpenes With 1-2 Oh) To Linear (And mentioning
confidence: 99%
“…Drug-release properties were evaluated in vitro, and the incorporation of Chol moiety in the Chol-PCL conjugate was found to improve cell proliferation. Additionally, PCL with a Chol moiety at both ends has been synthesized by coupling two monofunctional Chol-PCL conjugates to one hexamethylene diisocyanate [145]. This bifunctional conjugate has proven to be miscible with high MW PCL and thus is expected to be useful for the modification of PCL-based biomaterials.…”
Section: Cholesterol (And Other Terpenes With 1-2 Oh) To Linear (And mentioning
confidence: 99%
“…3,[23][24][25][26][27][28][29] Stupp and coworkers rst reported the synthesis of cholesterol end functionalized oligo(L-lactic acid). 3,23 Later, Cheng 24,25 and Yang 26 et al also reported cholesteryl end-capped aliphatic polycarbonates and dicholesteryl end functionalized block poly(3-caprolactone), respectively, as biodegradable polymers. These study results have shown that the cholesterol-functionalized biodegradable polycarbonate block copolymers can play an important role in encapsulation of complex hydrophobic therapeutics for drug application.…”
Section: Introductionmentioning
confidence: 99%
“…Stupp et al [ 28 ] first reported the synthesis of cholesterol end functionalized oligo(L-lactic acid) and its interaction with cells. Subsequently, Guo [ 29 ] and Cheng et al [ 30 ] reported cholesteryl end-capped aliphatic polycarbonates and dicholesteryl end functionalized triblock poly(ε-caprolactone), respectively, as biodegradable polymers. Recently, the cholesteryl-functional polymers have been applied in the field of nanomedicine, such as drugs or nucleic acids delivery, complex hydrophobic therapeutics, etc.…”
Section: Introductionmentioning
confidence: 99%